Dynamic mechanical thermal analysis of unaged and hygrothermally aged discontinuous Bouligand structured CFRP composites. (1st December 2022) - Nwambu, Chidume; Robert, Colin; Alam, Parvez
Abstract: A dynamic mechanical thermal analyser operating in the single cantilever mode was used to examine the dynamic mechanical properties of unaged and hygrothermally aged discontinuous asymmetric helicoidal (Bouligand) carbon fibre reinforced plastic (CFRP) composites as a function of fibre architecture. The discontinuous Bouligand was manufactured using two major pitch angles as independent variables: 90° and 120° and from each major pitch angle, minor interply pitch angles were used as independent variables ranging 5°–25°. The composites were tested as either dry unaged specimens or following hygrothermal ageing in seawater at the constant temperatures of 40 °C and 60 °C for over 2000 h. We find that the viscoelastic properties E ′ and E ″ are adversely affected by both hygrothermal aging and the minor pitch angle, but not the major pitch angle. Higher hygrothermal ageing temperatures and increasing minor pitch angles are found to decrease the energy absorption and dissipation capacities of discontinuous Bouligand structured CFRP composites. The tan- δ curves also indicate that hygrothermal ageing increases the heterogeneity of discontinuous Bouligand structured composites, with separate viscoelastic phases and glass transition temperatures.